Welder Qualification Requirements for Midship Block Assembly of a 3702 GT Barge - Mistipa Avin, Fabelyn Gandryal; Rachman, Taufiqur (Maritime Park: Journal of Maritime Technology and Society, 2026)
Precise and efficient welding is required in the assembly and erection of the 3702 GT barge block system. A mismatch between the number of welders available and actual needs in the field can affect production time and cost efficiency. The purpose of this study is to determine the number of welders and electrodes required in the assembly of the 3702 GT midship barge block, which is expected to serve as a reference in the planning and management of welders and materials in the shipbuilding process. A quantitative approach was taken by collecting technical data, namely welding length, fillet volume, welder productivity, and work efficiency. The data was obtained from technical documents, field measurements, and three-dimensional modeling of the 3702 GT midship barge block. The analysis results show that the total welding length in fabrication reaches 1.361 meters, while in erection it reaches 126 meters. with a welding volume of 31,184 cm³ and an electrode requirement of 326.39 kg. With the application of 35% work efficiency of welders in the field, the requirement for welders for the assembly of the midship barge block was eight welders with a duration of seven days.